KONTRIBUSI KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN INDIHOME DI KOTA PADANG - Ridwan Rasyid; Gustina Gustina; Ika Yuanita (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2022)
The very rapid development of technology, information, and communication in the current era of globalization is very helpful and facilitates the work of the world community, one of which is currently popular is the internet. This study aims to determine the contribution of service quality and product quality to Indihome customer satisfaction in the city of Padang. The methodology of this research is quantitative research. The sample in this study was 100 customers who were taken by the purposive sampling method. The analytical method used is multiple linear regression analysis. The results showed that simultaneously service quality and product quality had a positive and significant effect on Indihome customer satisfaction in the city of Padang. While partially the service quality variable has no significant effect on Indihome customer satisfaction in the city of Padang, and the product quality variable has a positive and significant effect on Indihome customer satisfaction in the city of Padang. Product quality is the most dominant variable affecting customer satisfaction.